The understanding of sad appeal in emotional advertisement among audiences in Klang Valley, Malaysia - Mohd Shahnawi Muhmad Pirus,; Sara Yazmin Zulqahar, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The rise in emotional advertising comes at a time when brands are making every effort in creating contents rather than just making advertisements. The aim of this study is related to advertisements that contain sad emotional appeals, and its impact on the viewers and their purchasing decisions. The research methodology of qualitative method and phenomenological approach were applied. The data of this study was then collected by conducting in-depth interview. The data from the interview session was transcribed verbatim to ensure the words and sentences are transcribed accordingly. The findings discuss the attitude shown by the audiences towards the emotional contents in advertisements. The attitude shown by the audiences was observed closely on their reactions after watching advertisements that contains emotional appeals; particularly sad appeals. In point of fact, this research has managed to reveal on the pattern involved among advertisement audiences in navigating the content from advertisements with emotional appeals. This study is predominantly a study of emotional advertisements; Sadvertisement, as catchy as it sounds, as a popular culture terminology that describes an advertising trend for consumers in which advertisers are using a certain set of game plan to jockey on people's emotions and galvanise feelings of sadness, melancholy or wistfulness. The study adheres to the idea of a growing number of emotional advertisements and its effect on the advertisement audiences.